Pocket park / Aida Tihani Azlan ... [et al.] - Azlan, Aida Tihani; Zulkifli, Jazmin; Mohd Halmy, Nur Iryanis; Mohd Zikrullah Shah, Syahirah Nabilah (2024)
Pocket Park furniture is an innovative solution that creates compact, multifunctional green spaces in urban areas. This study explores the design and benefits of these parks, focusing on their ability to integrate multiple functions into a single, space-saving unit. Key features, such as water harvesting systems that sustain plant growth and generate hydroelectricity, were analysed through a review of existing installations and case studies. The findings highlight how pocket park furniture maximizes urban space, enhances neighbourhood aesthetics, fosters social interaction, and contributes to environmental sustainability. Adopting these designs could significantly improve urban living, making cities greener and more community-oriented.